HUBUNGAN POLA ASUH ORANGTUA TERHADAP PERUBAHAN EMOSIONAL REMAJA DI SMP IT AL-KINDI PEKANBARU TAHUN 2019 - Andri Ani (ITKM WIDYA CIPTA HUSADA, 2020)
Teenagers is a transitional period in the span of human life, connecting right-childhood and adulthood which includes biological, cognitive, and social emotional changes. Old people are the main role takers in taking care of their children. Parenting is a pattern of behavior that parents use to connect with children. This study aims to” Relationship Between Parenting Parents Towards The Emotional Changes Of Adolescents In Junior High School It Of Al-Kindi Pekanbaru In 2019